Antithrombotic effect of Lonomia obliqua caterpillar bristle extract on experimental venous thrombosis - Prezoto, B.C.; Maffei, Francisco Humberto de Abreu [UNESP]; Mattar, L. [UNESP]; Chudzinski-Tavassi, A.M.; Curi, P.R. [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 2002)
The venom of Lonomia obliqua caterpillar may induce a hemorrhagic syndrome in humans, and blood incoagulability by afibrinogenemia when intravenously injected in laboratory animals. The possible antithrombotic and thrombolytic activities of L. obliqua caterpillar bristle extract (LOCBE) were evaluated in this study. The minimal intravenous dose of the extract necessary to induce afibrinogenemia and anticoagulation was 3.0 and 10.0 µg protein/kg body weight for rabbits and rats, respectively. In rabbits, this dose induced total blood incoagulability for at least 10 h and did not reduce the weight of preformed venous thrombi, in contrast to streptokinase (30,000 IU/kg). In rats, pretreatment with 5.0 and 10.0 µg/kg LOCBE prevented the formation of thrombi induced by venous stasis or by injury to the venous endothelium. The dose of 5.0 µg/kg LOCBE did not modify blood coagulation assay parameters but increased bleeding time and decreased plasma factor XIII concentration. When the extract was administered to rats at the dose of 10.0 µg/kg, the blood was totally incoagulable for 6 h. These data show that LOCBE was effective in preventing experimental venous thrombosis in rats, justifying further studies using purified fractions of the extract to clarify the mechanisms of this effect.
Keywords: Thrombosis; Fibrinolysis; Anticoagulant; Venom; Lonomia obliqua caterpillar